Marketing Strategy of a Multinational Company for Emerging Markets of CIS States - Bartes, Karel; Halík, Jaroslav, 1961-; Sedlacký, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2007)
The saturation of Western markets, strong and predatory competition, and the end of supranational state units, all these factors have contributed to eminent interest of multinational companies in the newly created markets of the Commonwealth of Independent States. For that reason, the thesis discusses marketing theories as well as a wide range of marketing strategies and tools tailored to local specific cosmetics markets based on executed situation analysis.
Vedoucí práce: Jaroslav Halík
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2008
Rok obhajoby 2008
Keywords: mezinárodní obchod [obor dipl. práce]; marketing; diplomové práce; marketing; master's theses